Cross-linkable molecule in spatial dimension boosting water-stable and high-efficiency perovskite solar cells. (March 2022) - Xi, Jiachen; Wu, Yeyong; Chen, Weijie; Li, Qilong; Li, Jiajia; Shen, Yunxiu; Chen, Haiyang; Xu, Guiying; Yang, Heyi; Chen, Ziyuan; Li, Na; Zhu, Jian; et al.
Abstract: Solution-processed perovskite films have high trap densities especially on the perovskite surface that become pathways of moisture invasion, unavoidably leading to perovskite degradation. Although the water resistance or crosslinking organic molecules attached to the perovskite film can partially mitigate the degradation, there is usually a significant trade-off between device power conversion efficiency (PCE) and moisture stability due to the insulating nature of the organic molecules. Here, we designed and synthesized a cross-linkable molecule PETA-G to solve the problem by rationally combining the guanidine and tri-acrylate groups. The guanidine group with three lone pair electrons enables sufficient bonding between lone pair electrons and undercoordinated Pb 2+ of the perovskite grain surface; the tri-acrylate group with three crosslink sites has a moderate crosslinking condition that can spatially crosslink, thus forming a compact network on the perovskite surface. The crosslinked PETA-G (CL-PETA-G) can significantly suppress non-radiative recombination and improve the moisture resistance of the perovskite film that even survives when dipped into water, while the charge transport was not influenced. Consequently, the long-term moisture and operational stabilities of the perovskite solar cells based on FA0.92 MA0.08 PbI3 with CL-PETA-G were dramatically increased, and the devices achieved a remarkable PCE as high as 22.6%. Graphical Abstract: We synthesized a cross-linkable molecule PETA-G combining the guanidine and tri-acrylate groups, which can spatially crosslink on the perovskite film to improve the moisture-resistance ability and passivate surface defects of perovskite film. ga1 Highlights: PETA-G can crosslink a framework in spatial dimension with high crosslinking degree on perovskite film. The crosslinking framework improves the water-resistance ability of perovskite film even immersing into water. PETA-G can repair the perovskite film morphology and electronic defects.